PENGGALIAN JIWA WIRAUSAHA DI UNIVERSITAS SLAMET RIYADI SURAKARTA - Yustina Wuri Wulandari, Dorothea Ririn Indriastuti & (ADI WIDYA : JURNAL PENGABDIAN MASYARAKAT, 2017)
Entrepreneurship was important study for student in Slamet Riyadi University. One of the mission of Slamet Riyadi University was to become Entrepreneur University and it was be course material in academic curriculum. This artichel shown entrepreneurship activity in Slamet Riyadi University for student in economic, agriculture, food technology and humaniora studies program.Keywords: entrepreneurship, academic curriculum